Punkte: Für orchester - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2009)
Stockhausen conducts PUNKTE for orchestra ( Archive No. 37 / 2 )(Colour film by Suzanne Stephens )Two performances of PUNKTE for orchestra on February 5th 1993 with the symphonyorchestra of the Hessen Radio, Frankfurt, conducted by Karlheinz Stockhausen and concert talk byStockhausen